Penetapan Waktu Wajib Zakat Fitrah Dalam Perspektif Fikih dan Ilmu Falak - Mahzan Mahzan; Ismail Ismail (Islamic Astronomy Department, Sharia and Law Faculty, 2023)
The determination of the mandatory time to issue zakat fitrah has been dominated by the perspective of jurisprudence, even though the time of issuing zakat fitrah is closely related to the Hijri calendar system. Currently, the criteria in the preparation of the Hijri calendar system have varied, in Indonesia alone, there are criteria for the true hisab of the hilal title, there are also the criteria for the true hisab of imkan rukyat, and there are also the criteria for the rukyah hilal. In the perspective of jurisprudence, the mandatory time to issue zakat fitrah is the night of 1 Shawwal for people who live from Ramadan to enter Shawwal, if one of the months is not found, then it is not mandatory to issue zakat fitrah for him. In terms of science, the beginning of the Hijri month is greatly influenced by the criteria used, there are hisab criteria and there are rukyat criteria. It is very likely that there is a difference in the determination of 1 Shawwal between the two criteria. This difference will have an impact on the mandatory time to issue zakat fitrah. This study concluded that the mandatory time to issue zakat fitrah depends on the criteria for determining the beginning of the Hijri month that he believes, so the difference in determining the mandatory time to issue zakat fitrah is very wide open as long as the criteria for the Hijri calendar have not been uniform.